(untitled) (Research, Society and Development, 2021)
Teaching contextualized with socio-scientific issues focused on the reality of students and combined with pedagogical practices that encourage reasoning, critical thinking and interaction, proves to be very productive in improving the learning of Biology and the formation of critical citizens. Aim to develop and apply an Investigative Teaching Sequence (SEI) with molecular biology practices as a problem-solving tool for teaching Genetics. The target audience was 70 students from the 3rd year of high school in the city of Canto do Buriti (PI). The qualitative-quantitative and interventional research consisted of the application of a SEI in six moments that aimed to encourage the student to research and share videos; investigate paternity simulations; set up a crime scene; perform DNA extraction and playful Molecular Genetics simulations, thus becoming the protagonist of the investigative process. Students asked open-ended questions associated with SEI moments. Qualitative observation evidenced the critical and investigative position of students in the face of problematization and scientific maturation, while quantitative analysis demonstrated the development of skills and understanding of the subject. Therefore, SEI facilitated the understanding of forensic genetics, minimizing the gap between theory and practice, as well as arousing greater interest among students in the study of Molecular Genetics.